El Excentrico, 1963-04-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
April 20, 1963 [20 de abril de 1963]. Ano 13, No 12. Cover has photograph of Hank Paramo and Gilbert Solarez, wearing suits made by Bill Hernandez Tailoring. The headline reads, "Hank Paramo and Gilbert Solarez wear the latest from Bill's."